Sosialisasi Penggunaan Media Pembelajaran Berbasis IT untuk Menanggulangi Dampak Covid-19 dalam Bidang Pendidikan - Hayani Wulandari; Turmudi Turmudi; Anggi Lestari Purnama; Deby Ifevayona Ginting; Dian Robiatussa’diyah; Gita Yulia Dewi; Nineu Erwinda Agustin; Nur Anisa Fitri Hasan; Sovana Dwi Lestari (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Information technology today is very much needed by every society, especially during the current pandemic. The development of information technology which is increasingly rapid in the current era of globalization cannot be avoided anymore its impact on the world of education. Global demands call upon the world of education to always and constantly adapt technological developments to the steps in improving the quality of education, especially adjusting its use for the world of education, especially in the learning process. There are many learning media technologies in the form of platforms that are used in every educational institution, at the school level to streamline the learning process carried out, such as classrooms, google forms, quizizz and zoom. PLSP Group of the Indonesian Education University, Purwakarta Campus, endeavors to solve problems through extension programs and instructional media training for teachers. The goal is that the skills of teachers in making teaching materials using learning media based on information technology and the internet can be improved.